2021
DOI: 10.1093/hmg/ddab225
|View full text |Cite
|
Sign up to set email alerts
|

A conserved ATG2 binding site in WIPI4 and yeast Hsv2 is disrupted by mutations causing β-propeller protein-associated neurodegeneration

Abstract: PROPPINs are phosphoinositide-binding β-propeller proteins that mediate membrane recruitment of other proteins and are involved in different membrane remodeling processes. The main role of PROPPINs is their function in autophagy, where they act at different steps in phagophore formation. The human PROPPIN WIPI4 (WDR45) forms a complex with ATG2 involved in phagophore elongation, and mutations in this gene cause β-propeller protein-associated neurodegeneration (BPAN). The yeast functional counterpart of WIPI4 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 73 publications
(99 reference statements)
2
13
0
Order By: Relevance
“…Missense and additional C-terminal truncating mutations were obtained by using mutagenic PCR. pmCherry-SNX5 and pEGFP-SNX5 were generated by cloning the full-length SNX5 coding sequences in the polylinker of pmCherry ( Bueno-Arribas et al, 2021 ) and pEGFP-C3 ( GenBank Accession Number # U57607 ). VPS13A fragments were obtained by PCR and inserted into pEGF-C3.…”
Section: Methodsmentioning
confidence: 99%
“…Missense and additional C-terminal truncating mutations were obtained by using mutagenic PCR. pmCherry-SNX5 and pEGFP-SNX5 were generated by cloning the full-length SNX5 coding sequences in the polylinker of pmCherry ( Bueno-Arribas et al, 2021 ) and pEGFP-C3 ( GenBank Accession Number # U57607 ). VPS13A fragments were obtained by PCR and inserted into pEGF-C3.…”
Section: Methodsmentioning
confidence: 99%
“…75 Accumulating evidence from recent studies show that both WIPI3 and WIPI4 can interact with ATG2A via the WIR (WIPI-interacting-region) motif. 33,[81][82][83] Further studies show that the WIPI3/WIPI4-ATG2A complex serve to establish the contact sites between ER and phagophore, enabling the transportation of lipids to promote phagophore expansion. [33][34][35] Moreover, WIPI3/WIPI4-ATG2A complex is also involved in autophagosome-lysosome fusion, 84 adding to the complexity of the WIPIs functions.…”
Section: 12mentioning
confidence: 99%
“…Recently, it has been reported that WIPI3, similar to WIPI2, is also able to interact with ATG16L1 to promote LC3B lipidation 75 . Accumulating evidence from recent studies show that both WIPI3 and WIPI4 can interact with ATG2A via the WIR (WIPI‐interacting‐region) motif 33,81–83 . Further studies show that the WIPI3/WIPI4–ATG2A complex serve to establish the contact sites between ER and phagophore, enabling the transportation of lipids to promote phagophore expansion 33–35 .…”
Section: Molecular Mechanisms In Control Of Autophagymentioning
confidence: 99%
“…Another member of the yeast PROPPIN family is Hsv2. Recent reports suggest that, under basal conditions, Hsv2 colocalize with a pool of Atg2 on endosomes whereas upon autophagy induction, the colocalization happens at PAS (Bueno‐Arribas et al, 2021, p. 2).…”
Section: Autophagy Pathwaymentioning
confidence: 99%